Choreography in the art education system: modern Ukrainian and world practice - Bigus, Olga; Bazela, Dmytro; Pidlypska, Alina; Bilash, Olha; Yefanova, Svitlana; Khodakivska, Nataliia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this study was to investigate the system of art education and its role in the conservation and dissemination of culture in a globalized world, and to find out the current scenario of dance forms and the way they are affected by global developments and their future. This study was also aimed to focus on the teaching of these art forms, as well as modern and foreign dance forms in Ukraine and around the world, and to examine the element of choreography in modern arts education. Both qualitative as well as quantitative methods of data collection were used. Data collection took the form of primary research (a survey consisting of 2 questions related to dance education and choreography) and secondary research (a set of 11 major articles). The survey was conducted on 51 dancers (teachers and students of fine arts) and the questionnaire data were analyzed using descriptive analysis. Artists of pure traditional descent still believe in reviving traditional forms of dance in their true form, rather than combining them with other contemporary styles. The participants were of the opinion that the popularity of dance education is falling in popularity over the years, and also do not see the fusion genre of choreography as authentic or sharing the traditional or cultural values of the traditional dance forms. The results also showed that the system of art education is an efficient manner of transferring knowledge about the choreography of traditional and modern dance forms all across the world and that people associate traditional dance forms with cultural identity. Our study indicated a continuing legacy of art education for dance forms and their choreography for the coming generations, also the continuous existence of the traditional and modern art forms in their original and fused forms.